2011
DOI: 10.1007/s10526-011-9430-2
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of aphids, whiteflies and their natural enemies under photoselective nets

Abstract: Integrated Pest Management of insects includes several control tactics, such as the use of photoselective nets, which may reduce the flight activity of insects. Limiting the dispersal of pests such as aphids and whiteflies is important because of their major role as vectors of plant viruses, while a minor impact on natural enemies is desired. In this study, we examined for the first time the dispersal ability of three vector species, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Macrosiphum euphorbiae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
4
24
0
8
Order By: Relevance
“…Results from experiments carried out in cages covered with UV-absorbing nets showed that visual cues in Orius laevigatus (Fieber) (Hemiptera: Anthocoridae) may be disturbed under UV-absorbing covers, inducing a reduction in dispersal. UV-deficient environments formed under photoselective screens seem to be attractive for Amblyseius swirskii (Athias-Henriot) (Acari: Phytoseiidae) (Legarrea, Weintraub, et al, 2012). It was suggested that the predatory mite attempts to avoid UV-B radiation that may reduce survival, egg laying, and hatching, as has been found for other predatory mite species (Onzo, Sabelis, & Hanna, 2010).…”
Section: Effect Of Uv Filtration On Insect Natural Enemiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Results from experiments carried out in cages covered with UV-absorbing nets showed that visual cues in Orius laevigatus (Fieber) (Hemiptera: Anthocoridae) may be disturbed under UV-absorbing covers, inducing a reduction in dispersal. UV-deficient environments formed under photoselective screens seem to be attractive for Amblyseius swirskii (Athias-Henriot) (Acari: Phytoseiidae) (Legarrea, Weintraub, et al, 2012). It was suggested that the predatory mite attempts to avoid UV-B radiation that may reduce survival, egg laying, and hatching, as has been found for other predatory mite species (Onzo, Sabelis, & Hanna, 2010).…”
Section: Effect Of Uv Filtration On Insect Natural Enemiesmentioning
confidence: 97%
“…CYSDV incidence under the UV-absorbing films was 2% compared to 14% under an ordinary film (Mizrahi et al, 1998). Infection rates of the nonpersistent viruses Cucumber mosaic virus (CMV) and Lettuce mosaic virus were lower under UV-absorbing screens, probably due to the lower population density and dispersal rate of the aphid vector M. euphorbiae (Legarrea, Betancourtb, et al, 2012;Legarrea, Weintraub, Plaza, Viñuela, & Fereres, 2012).…”
Section: Effect Of Uv Filtration On the Spread Of Insect-vectored Virmentioning
confidence: 99%
“…A pesar de que existen estudios que afirman que el uso de barreras fotoselectivas es compatible con algunas especies de organismos de control biológico, como Orius laevigatus (Fieber) (Heteroptera: Anthocoridae), Aphidius colemani Viereck, Aphidius ervi Haliday, Aphidius matricariae (Haliday) (Hymenoptera: Braconidae), Diglyphus isaea Walker (Hymenoptera: Eulophidae) y E. formosa (Chyzik et al, 2003;Chiel et al, 2006;Doukas & Payne, 2007c;Legarrea et al, 2012aLegarrea et al, , 2014, éstas pueden tener un efecto negativo en algunas especies como E. mundus, al interferir con su orientación, lo que ocasiona una disminución de la depredación y la parasitación de los insectos plaga (Chiel et al, 2006).…”
Section: Métodos Físicos De Control De B Tabaci En Cultivos Hortícolasunclassified
“…Numerosos autores han puesto de manifiesto el excelente control de dichas barreras sobre distintas plagas tales como pulgones, moscas blancas, trips, ácaros y minadores de hojas, así como de los virus transmitidos por las mismas (Antignus et al, 1996(Antignus et al, , 1998(Antignus et al, , 2001Chyzik et al, 2003;Fereres et al, 2003;Kumar & Poehling, 2006;Doukas & Payne, 2007b;Legarrea et al, 2012aLegarrea et al, , 2012b.…”
Section: Introductionunclassified
See 1 more Smart Citation